Women in Management: Trends, Issues, and Challenges in Managerial Diversity/Competitive Frontiers: Women Managers in a Global EconomyWomen in Management: Trends, Issues, and Challenges in Managerial Diversity, edited by FagensonEllen A.. Newbury Park, CA: Sage, 1993.Competitive Frontiers: Women Managers in a Global Economy, edited by AdlerNancy J.IzraeliDafna. Cambridge, MA: Blackwell. 1994. - Jacobson, Sarah (Academy of Management Review, 1995)
The article reviews the books “Women in Management: Trends, Issues, and Challenges in Managerial Diversity,” edited by Ellen A. Fagenson and “Competitive Frontiers: Women Managers in a Global Economy,” edited by Nancy J. Adler and Dafna Izraeli.